Stem cell therapies in post-prostatectomy erectile dysfunction: a critical review - (:unkn) unknown (CANADIAN J UROLOGY, 2017)
Introduction: Erectile dysfunction (ED) is still a common complication of radical prostatectomy. Current treatments of ED are mainly symptomatic. Mesenchymal stem cells (MSCs) have been widely investigated as a potential curative treatment. Although MSC therapy consistently improved erectile functions in the pre-clinical studies the initial expectations seem to be unmet. The aim of this study is to critically review the existing studies on use of stem cells in post-prostatectomy ED and understand factors that preclude clinical translation of the available evidence. Materials and methods: A literature search for all preclinical and clinical studies investigating MSCs in the treatment of post-prostatectomy ED published between January 2009 and March 2016 was performed using the PubMed database. Results: A total of 24 pre-clinical studies investigated MSC based treatments in cavernous nerve injury (CNI) rodent models. In the majority of these studies intracavernous injection of MSCs at the time injury improved erectile functions. There is less data on the efficacy of MSCs when applied in a chronic disease state. Allogeneic or xenogeneic MSCs were similarly effective with limited data on immunologic response. There is a lack of conclusive data on in vivo fate of MSCs and the best route of MSC administration. Conclusion: MSC therapy consistently improved erectile functions after CNI. There seems to be a consensus on the disease model used and outcome evaluation however further studies focusing on immunologic response to MSCs, their mechanism of action and in vivo fate are needed before their widespread use in clinic.
Keywords: radical prostatectomy; cavernous nerve injury; mesenchymal stem cells; erectile dysfunction; MESENCHYMAL STROMAL CELLS; RAT MODEL; RADICAL PROSTATECTOMY; VASCULAR FRACTION; FUNCTION RECOVERY; IN-VITRO; PERIPROSTATIC IMPLANTATION; INTRACAVERNOSAL INJECTION; PENILE ERECTION; EXPRESSION